STUDI PEMBUATAN MAKANAN PENDAMPING ASI (MP-ASI) MENGGUNAKAN CAMPURAN TEPUNG KECAMBAH KACANG KEDELAI, KACANG HIJAU, DAN BERAS - Purwanto -; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2011)
Beans (soy beans, green beans) and cereals (rice) in the form of sprouts can improve the digestibility during germination occurs due to hydrolysis of carbohydrates, proteins and fats into simpler compounds, so it is easy to digest. During this process a rapid increase in the amount of protein and vitamins, while fat content decreased. Sprouts in the form of flour can be used as an ingredient mixture of complementary food of Mother’ Breast. The purpose of this study to determine levels of protein, vitamin C, and organoleptic properties of foods AS1 (MP-ASI) of soybean sprout flour mixture, green beans, and rice. The experimental design in this study using a completely randomized design with 8 treatments and 3 replication as for the experimental design as follows: BKK1 (25%: 75%), BKH2 (25%: 75%), BKK3 (50%: 50%), BKH4 (50%: 50%), BKK5 (75%: 25%), BKH6 (75%: 25%), BKHKK7 (50%: 25%: 25%), BKHKK8 (25%: 25%: 50%), data analysis, protein content, levels of vitamin C using Anova statistical test and further test DMRT organoleptic properties while analysis using friedman test and further test Wilcoxon. The results showed the effect of variation in flour mixture soybean sprouts, green beans, and rice in the manufacture of complementary feeding on levels of protein, vitamin C, and organoleptic properties. Levels of protein and vitamin C in a mixture BKHKK8 highest (25% germination of rice flour: 225% sprouted mung bean flour: 50% soybean sprout flour) of 23.29 g% and organoleptic assessment of vitamin C while the average panelist liked the mix of products BKK5 (75% germination of rice flour: 25% soybean sprout flour).